2017
DOI: 10.1097/aln.0000000000001620
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine and Propofol on Basal Ganglia Activity in Parkinson Disease

Abstract: Background Deep brain stimulation electrodes can record oscillatory activity from deep brain structures, known as local field potentials. The authors’ objective was to evaluate and quantify the effects of dexmedetomidine (0.2 μg·kg-1·h-1) on local field potentials in patients with Parkinson disease undergoing deep brain stimulation surgery compared with control recording (primary outcome), as well as the effect of propofol at different estimated peak effect site concentrations (0.5, 1.0, 1.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 33 publications
5
41
0
1
Order By: Relevance
“…Our finding coincides with previous computational modelling and animal studies showing increased frontal corticothalamic alpha coherence associated with consciousness 13,39 . Our results are also consistent with the previous study showed reduced beta band activity in STN during general anaesthesia 19 . Furthermore, our results highlighted more comprehensive changes in STN during general anaesthesia and intubation, which was not observed in the cortical EEG, suggesting a more complicated role of STN in the modulation of consciousness.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding coincides with previous computational modelling and animal studies showing increased frontal corticothalamic alpha coherence associated with consciousness 13,39 . Our results are also consistent with the previous study showed reduced beta band activity in STN during general anaesthesia 19 . Furthermore, our results highlighted more comprehensive changes in STN during general anaesthesia and intubation, which was not observed in the cortical EEG, suggesting a more complicated role of STN in the modulation of consciousness.…”
Section: Discussionsupporting
confidence: 94%
“…Recent investigation on the connectivity within the cortico-basal ganglia-thalamo-cortical network has shown that propofol-induced unconsciousness modulated the pallidal connectivity to the posterior cingulate cortex, suggesting the role of pallido-cortical connectivity in altered states of consciousness 17 . Recent study also showed that propofol significantly modulated the oscillatory neuronal activity in the beta frequency band in the STN 19 . However, electrophysiological brain activity consists of rhythmic oscillation and arrhythmic activity indicative of the oscillatory and fractal dynamics, respectively, arising from likely distinct neural basis [20][21][22] .…”
Section: Introductionmentioning
confidence: 88%
“…Propofol, a GABAergic agent, has been most frequently used when sedation is required. As stated before, several clinical reports showed a dose-dependent effect of propofol on STN neuronal activity in patients with PD [7][8][9]20]. Propofol reduces neuronal activity by enhancing inhibitory neurotransmission and reducing excitatory neurotransmission [21].…”
Section: Effect Of Procedural Sedation and Analgesia On Micro-electromentioning
confidence: 75%
“…It exerts its clinical effect through an agonist effect on the gamma-aminobutyric acid type A (GABA A ) receptor [6]. Several studies have shown that GABAergic agents alter STN activity in a dose-dependent manner [7][8][9]. In the past decade experience has been gained with non-GABA-mediated agents, including the α 2 -agonists clonidine (CLONI) and dexmedetomidine (DEX), which possess sedative and mild analgesic effects, and the ultrashort acting opioid, remifentanil (REMI) which provides potent analgesia and mild sedation.…”
Section: Introductionmentioning
confidence: 99%
“…All of our patients were able to wake up quickly and cooperated with neurological tests. Dexmedetomidine could reduce anxiety, airway sensitivity and increase analgesic effects but had no significant impact on MER monitoring [5, 6]. Finally, DBS was performed in the supine position and the airway was easily accessible to the anesthesiologist.…”
Section: Discussionmentioning
confidence: 99%